Pengaruh Audit Tenure, Umur Publikasi, Rotasi Audit terhadap Kualitas Audit : Studi Empiris pada Perusahaan Sektor Pertambangan Tahun 2019-2023 - Ramadona, Miftahul; Taqwa, Salma (Universitas Negeri Padang, 2025)
This research examines the association of audit tenure, Publication Age, Audit Rotation as independent variables on audit quality. This research was conducted mining sector company listed on the Indonesia Stock Exchange from 2019-2023. This research is important to do considering the literature review shows inconsistent results on each research variable. The research sample was selected through purposive sampling method and using logistic regression as the basis of analysis. The results of the research and hypothesis testing that have been carried out show that the first hypothesis is accepted where there is no influence between audit tenure and the quality of audit results. the second hypothesis is rejected where there is no influence between the publication age on audit quality. the third hypothesis is rejected where there is no influence between audit rotation on audit quality.